Development of Poetry Writing Materials Based on Learning Videos in UPTD SDN 017135 Sengon Sari - Suryanti Indrayani, Novi; Laut Hasibuan, Ahmad; Sutikno; Rahmat Kartolo (PT Inovasi Pratama Internasional, 2026)
This research aims toTo find out the results of developing poetry writing material based on learning videos that can motivate fifth grade students at UPTD SDN 017135 SENGON SARI. In addition, to find out the validation of the development of poetry writing material based on learning videos by fifth grade students at UPTD SDN 017135 SENGON SARI and to find out the effectiveness of poetry writing material based on learning videos by fifth grade students at UPTD SDN 017135 SENGON SARI in the 2024-2025 academic year. This study uses the Sugiono model development method (Research & Development), with the subject of this poetry writing material being the validator. The assessment is carried out with a validation system that has been designed by the researcher. The validators in this study are material expert lecturers and learning video experts at UMN ALWASHLIYAH MEDAN. The subjects of this study are fifth grade students at UPTD SDN 017135 SENGOAN SARI in the 2024-2025 academic year. The validation results by students, class teachers and a team of material and video experts obtained a score of 100% categorized as good. The poetry writing teaching material is also effectively used in UPTD SDN 017135 SENGON SARI, with the category before the development of this material, students were unable to create free poetry with the category of less able, then improved to good after this development product was used in learning to write free poetry